Implementation of Build Back Better (BBB) Framework in Achieving Sustainable Development Goals: Case Study: Housing Reconstruction at Duyu Urban Village, Palu City, Central Sulawesi Province - Ayu Erlinna; Djoko Santoso Abi Suroso; Kim Dowon (The Journal of Indonesia Sustainable Development Planning, 2020)
The occurrence of 7.5M earthquake and tsunami in Central Sulawesi in September 2018 resulted in2,045 fatalities and 67,310 damaged houses. In line with RIPBand SDGSs 11, the government has established a masterplan for rehabilitation and reconstruction of Central Sulawesi by adopting the build back better concept. This research triesto analyze the implementation of BBB framework which focuseson reducingthe risk ofhousing reconstruction in Duyu urban village, using the scale and index method. The result shows that the implementation of risk reduction fallsinto a moderate level although some indicators are still in the poor category. In accordance with SDGs, at least four key factorsrelated to disaster mitigation, specificallySDGs 11 –makingcities and human settlements inclusive, safe, resilient and sustainable -havebeen successfully achieved,which are: 11.5; 11.b1; 11.b2; and 11.c1. This result indicates that the Duyu housing reconstruction has gone through analysis and consideration ofrisk reduction practicesinvolvingfive variables by adopting the BBB framework in creating community resilience while achieving SDGs in Indonesia.